Primary Malignant Fibrous Histiocytoma of the Chest Wall Misdiagnosed as Traumatic Hemothorax - Hwang, Ki-Eun (The Korean Academy of Tuberculosis and Respiratory Diseases, 2014)
Malignant fibrous histiocytoma (MFH), a type of sarcoma, is a malignant neoplasm with uncertain origins that arise from both the soft tissues and the bone. The occurrence of MFH on the chest wall is extremely rare. We hereby report a case of a 72-year-old woman who was incidentally detected with MFH after a traffic accident.